A Simulation Method Suited for the Whole French Territory Electromagnetic Waves Exposure - Noé, Nicolas; Sefsouf, Lydia; Dufour, Jean-Benoit; Carré, Samuel; Conil, Emmanuelle; Bounoua, Nabila; Agnani, Jean-Benoit (Comptes Rendus. Physique, 2024)
As part of the process for monitoring public exposure to electromagnetic waves, the national frequency Agency is carrying out, in collaboration with the Ministry of Ecological Transition and Territorial Cohesion, the Scientific and Technical Center for Building (CSTB) and Geomod, a numerical modeling of the electromagnetic wave exposure levels emitted by mobile telephony base stations on a national scale. This paper presents a dedicated simulation method for the numerical modeling of the whole French territory’s exposure to EMF. This method accounts for EMF exposure everywhere (outdoors and inside buildings), while performing fast enough to fulfill operational constraints. The simulation method relies on a ray-based 2.5D and 3D mixed approach that takes into account computation areas depending on the radiated power pattern of the antennas. The method is yet deployed on pilot areas before a full deployment.